Comparison of Beaming Screw Outcomes with and without Subtalar Arthrodesis in Midfoot Charcot Reconstruction. Issue 4 (16th October 2019) - Ahn, Junho; Wukich, Dane K.; Liu, George T.; Raspovic, Katherine M.; VanPelt, Michael D.; Lalli, A.
Category: Diabetes, Midfoot/Forefoot Introduction/Purpose: Charcot neuroarthropathy (CN) is a complication of neuropathy secondary to diabetes mellitus (DM) and may involve multiple joints of the foot, in particular the midfoot. Patients with CN deformity associated with infection, ulceration or pre-ulceration are at risk of losing their limb. In these patients, reconstruction of the foot structure through beaming arthrodesis screws for stabilization is often required. In addition to midfoot beaming, previous reports have advocated for subtalar arthrodesis. Fixation of the subtalar joint restricts motion of the hindfoot. This rigid fixation has been hypothesized to offer greater stability and fewer hardware failures. The aim of this study was to describe failure of midfoot beaming screws after midfoot reconstruction of CN with and without subtalar arthrodesis. Methods: We retrospectively reviewed patients with DM diagnosed with CN. Patient radiographs were evaluated for type of midfoot Charcot reconstruction and hardware failure. Patients included in the study had follow up of 3 months or more. The main outcome variable of interest was hardware breakage. Results: Eighteen patients who underwent midfoot reconstruction for CN were included. The average age was 52.7 years (±8.4 years), 10 (55.6%) were male, and the average body-mass index (BMI) was 35.8 kg/m2 (±10.3 kg/m2). The average follow-up time was 6.5 months (±3.7 months). In the current series, thirteen out of 18 (72.2%) patients underwent subtalar fusion along with midfoot fusion. Screw breakage occurred in two patients, one at the 1st tarsometarsal joint and 2nd-4th tarsometarsal screws in another patient at 9 and 6 months respectively. Both patients with screw breakage had subtalar fusion. A third patient who had subtalar fusion subsequently developed collapse of their talus leading to subtalar screw removal 3 months after initial surgery. Patients without subtalar fusion did not experience screw breakage. Conclusion: An extended medial column fixation with subtalar arthrodesis has been previously proposed to provide better fixation after midfoot CN reconstruction with beaming screws as it restricts motion of the hindfoot. However, little to no evidence has been reported in favor of this technique. Our findings suggest that subtalar arthrodesis may result in fixation that is too rigid, which may place the beaming screws at higher risk of breakage. However, the number of observations is a limitation of our study, and further investigation comparing these techniques is needed to fully evaluate the effect of subtalar arthrodesis on midfoot beaming outcomes.